2005
DOI: 10.5326/0410003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clomipramine on Cats Presented for Urine Marking

Abstract: Twenty-five cats exhibiting at least four episodes of vertical urine marking per week were assessed. Following a medical workup, a 4-week clomipramine trial was instituted, using a mean dose of 0.54 mg/kg per os q 24 hours. No concurrent behavioral or environmental modifications were applied. There was a statistically significant (P<0.0001) decrease in urine spraying when the cats were on clomipramine, with 20 of 25 cats having a > or =75% reduction in spraying within 4 weeks. Side effects were mild. Twenty ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…The number of cats living within each multi-cat household varied, for example, Frank et al [2] reported a range of 2-14 cats per household with a mean of 4.5 and a median of 3. A proportion of studies only recruited cats from multi-cat households with # 4 cats [18,21,33].…”
Section: Types Of Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of cats living within each multi-cat household varied, for example, Frank et al [2] reported a range of 2-14 cats per household with a mean of 4.5 and a median of 3. A proportion of studies only recruited cats from multi-cat households with # 4 cats [18,21,33].…”
Section: Types Of Participantsmentioning
confidence: 99%
“…Cats entering the study were either veterinary referrals or screened for underlying physiological complications that could influence spraying behaviour or interfere with the evaluation of the treatment. Cats were enrolled with evidence of feline lower urinary tract disease and other concurrent medical disorders (see Frank et al [2] and Landsberg and Wilson [33] for examples).…”
Section: Types Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoxetine, buspirone, clomipramine and paroxetine are often used as an initial treatment choice. 26,40,[49][50][51][52] If you are uncertain which agent to use, additional reading or consultation with a veterinary behaviorist will facilitate your selection.…”
Section: Separation Of Social Groupsmentioning
confidence: 99%
“…One of the RCT studies did not provide raw data for the placebo control group [19] thus only the data from the treated group could be used in the analysis. Four studies were open-label one-group pre and post designs [2], [5], [32], [33]. One study included a within subjects control group [1].…”
Section: Resultsmentioning
confidence: 99%